(untitled) (Fiep Bulletin - online, 2011)
It is increasing the number of people who look for physical practices in academy of gymnastics, glimpsing aesthetic, therapeutic and recreation objectives and, with rare competitive exceptions. Nevertheless, whatever is the goal to be reached; it has to be clear about the criteria and guidelines for the preparation of a planning based on the scientific knowledge. The training preriodization, arose out of the sport, shows it self as an element of great importance in the preparation of the strength training programs. Thus, the study has as objective: Identify the use of periodization by teachers when developing programs of strength training in gymnastics academies of Goiania’s city. It is a study based on the area of work and a study that used the method of description. The study included 6 teachers of weight training, 3 of each academy surveyed, half male and half female, with an average age of 25.8 + 4.07 years, and with an average of 6 + 4.43 years of experience in the area, so they are consequently characterized experienced. The vast majority has a degree in physical education and lato-sensu post-graduated in areas related to health, fitness centre and training. And they also, update their knowledge in these areas. However, the teachers present difficulties in conceptualizing some basic physical training principles and also, to set guidelines and criteria used for the preparation of a strength training based on scientific knowledge. Great fragility was identified when they conceptualize the periodization and its importance in the strength training programs. Simultaneously with these data, the teachers do not use the periodization in the elaboration of the training programs, because of the excessive number of pupils at the fitness centres , for the lack of pupils’ diligence, excessive workload, difficulties of intervention in their practice and due to lack of theoretical knowledge about the assumptions of a training program periodization.